Neuroprotective Effect of the Inhibitor Salubrinal after Cardiac Arrest in a Rodent Model - Jincheng Zhang (Oxidative Medicine and Cellular Longevity, 2020)
Cardiac arrest (CA) yields poor neurological outcomes. Salubrinal (Sal), an endoplasmic reticulum (ER) stress inhibitor, has been shown to have neuroprotective effects in both in vivo and in vitro brain injury models. This study investigated the neuroprotective mechanisms of Sal in postresuscitation brain damage in a rodent model of CA. In the present study, rats were subjected to 6 min of CA and then successfully resuscitated. Either Sal (1 mg/kg) or vehicle (DMSO) was injected blindly 30 min before the induction of CA. Neurological status was assessed 24 h after CA, and the cortex was collected for analysis. As a result, we observed that, compared with the vehicle-treated animals, the rats pretreated with Sal exhibited markedly improved neurological performance and cortical mitochondrial morphology 24 h after CA. Moreover, Sal pretreatment was associated with the following: (1) upregulation of superoxide dismutase activity and a reduction in maleic dialdehyde content; (2) preserved mitochondrial membrane potential; (3) amelioration of the abnormal distribution of cytochrome C; and (4) an increased Bcl-2/Bax ratio, decreased cleaved caspase 3 upregulation, and enhanced HIF-1α expression. Our findings suggested that Sal treatment improved neurological dysfunction 24 h after CPR (cardiopulmonary resuscitation), possibly through mitochondrial preservation and stabilizing the structure of HIF-1α.